Co-presence Analysis and Economic Patterns: Mediterranean Imports in the Celtic World - Feugnet, Aurélia; Rossi, Fabrice; Filet, Clara (Frontiers in Digital Humanities, 2017)
This article presents one of the first steps of a project that aims at exploring the diffusion patterns of Mediterranean imported goods in Late Iron Age Europe (250–25 BC) and the organization of the commercial interactions of these goods. It brings together two archeologists and a mathematician in the study of a large inventory of 57,735 Italian and Greek imports discovered from England to Serbia. This large amount of new and unpublished data is analyzed through the joint use of network analysis tools and formal statistical methods. The analysis focuses on detecting patterns in the association of imported artifacts that are often found on the same sites. The objectives are to highlight groups of imports that may have circulated together and to emphasize regional selections by local populations. At this stage of the study, two main systems of imports have been highlighted used, respectively, in West and Central Europe. Interesting leads that will need further investigation include the imports status and the role they played in Celtic societies, as acculturated objects or more as objects for acculturation.